Improved potency and selectivity of an oncolytic E1ACR2 and E1B19K deleted adenoviral mutant in prostate and pancreatic cancers - Oberg, Daniel; Yanover, Eva; Adam, Virginie; Sweeney, Katrina; Costas, Celina; Lemoine, Nick R; Halldén, Gunnel (Clinical cancer research, 2010)
Replication-selective oncolytic adenoviruses are a promising class of tumor-targeting agents with proven safety in hundreds of patients. However, clinical responses have been limited and viral mutants with higher potency are needed. Here, we report on the generation of a novel set of mutants with improved efficacy in prostate and pancreatic carcinoma models. Currently, no curative treatments are available for late-stage metastatic prostate or rapidly progressing pancreatic cancers. Adenovirus type 5 mutants were created with deletions in the E1ACR2 region for tumor selectivity and/or the E1B19K gene for attenuated replication in vivo; all constructs retain the E3 genes intact. Cell-killing efficacy, replication, and cytotoxicity in combination with chemotherapeutics were investigated in normal cells (PrEC and NHBE), seven carcinoma cell lines, and human (PC3 and DU145) and murine (TRAMPC, CMT-64, and CMT-93) tumor models in vivo. The double-deleted AdDeltaDelta (DeltaE1ACR2 and DeltaE1B19K) mutant had high cell-killing activity in prostate, pancreatic, and lung carcinomas. Replication was similar to wild-type in all tumor cells and was attenuated in normal cells to levels less than the single-deleted AdDeltaCR2 mutant. AdDeltaDelta combined with the chemotherapeutics docetaxel and mitoxantrone resulted in synergistically enhanced cell killing and greatly improved antitumor efficacy in prostate xenografts in vivo. In murine immunocompetent in vivo models efficacy was greater for mutants with the E3B genes intact even in the absence of viral replication, indicating attenuated macrophage-dependent clearance. These data suggest that the novel oncolytic mutant AdDeltaDelta is a promising candidate for targeting of solid tumors specifically in combination with chemotherapeutics.